Little Jack Rabbit and Danny Fox - Cory, David, 1872-1966; Barbour, Harold S., 1889-1961 (Salt Lake City, UT : Project Gutenberg, 2016)
"Little Jack Rabbit and Danny Fox" by David Cory is a children's book written in the early 20th century. This delightful story follows the adventures of Little Jack Rabbit as he interacts with a cunning fox named Danny, and it explores themes of friendship, cleverness, and the importance of being cautious. The book is part of the "Little Jack Rabbit Books" series, which encompasses various escapades of the titular character. The narrative begins with Little Jack Rabbit's encounter with Danny Fox, who lures him into a precarious situation under the guise of friendship. As the story unfolds, Jack Rabbit must navigate numerous challenges, including escapes from predators and clever tricks to outsmart the cunning fox. The tale introduces various animal characters, adding depth and intrigue to Jack's journey. Through a series of daring escapades, Little Jack Rabbit manages to outwit Danny Fox, demonstrating both bravery and clever thinking. Ultimately, the story emphasizes resilience and the value of being mindful of one's surroundings, making it an engaging read for children. (This is an automatically generated summary.)
Release date is 2016-08-27
E-text prepared by David Edwards and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive (https://archive.org)
Keywords: Animals -- Juvenile fiction; Rabbits -- Juvenile fiction; Foxes -- Juvenile fiction